Efficacy of non-pharmacological interventions for procedural pain relief in adults undergoing burn wound care: A systematic review and meta-analysis of randomized controlled trials. Issue 7 (November 2018) - Scheffler, Michael; Koranyi, Susan; Meissner, Winfried; Strauß, Bernhard; Rosendahl, Jenny
Highlights: This work reviews the effects of non-pharmacological interventions in burn patients. Non-pharmacological interventions might be a valuable adjunct to standard burn care. Benefits on procedural pain relief and mental distress reduction are demonstrated. Particularly virtual reality distraction and hypnosis could be recommended. Abstract: The aim of the present meta-analysis was to investigate the efficacy of non-pharmacological interventions for procedural pain relief in adults undergoing burn wound care compared to standard care alone or an attention control. Through a comprehensive literature search in various electronic databases 21 eligible randomized controlled trials (RCTs) were included, comprising a total of 660 patients. Random effects meta-analyses revealed significant positive treatment effects on pain outcomes, Hedges' g = 0.58, 95% CI [0.33; 0.84]. Heterogeneity of study effects was substantial, I 2  = 72%. Effects were significantly larger for comparisons against treatment as usual (TAU), g = 0.69, CI 95% [0.40; 0.98] than for comparisons against attention control groups, g = 0.21 [−0.11; 0.54], p < 0.001. Distraction interventions, particularly those using virtual reality, and hypnosis revealed the largest effects on pain relief. Non-pharmacological interventions further resulted in a significant small, homogeneous effect on anxiety reduction, g = 0.36 [0.20; 0.52]. In summary, benefits of non-pharmacological interventions on procedural pain relief and reduction of mental distress were demonstrated. Results have been proven to be free of publication bias. However, further high quality trials are needed to strengthen the promising evidence.